Development of nanocrystalline cellulose/graphene oxide based composite thin film for metal ions detection using surface plasmon resonance spectroscopy - Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim (2022)
Increasing metal ion contamination in the environment can cause severe effects towards human health. Hence, it is important to detect metal ion at low concentration for continuous monitoring of the surrounding environment. In this study, nanocrystalline cellulose/graphene oxide (NCC/GO) based thin film has been developed for metal ion sensing using surface plasmon resonance (SPR) technique. The properties of the NCC/GO thin film was confirmed by Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS) by showing all the functional groups of the composite. Moreover, the atomic force microscopy (AFM) result shows that the thin film roughness increased after the combination of NCC and GO. Conversely, the optical properties of the NCC/GO thin film were characterized by Ultraviolet-Visible spectroscopy (UV-Vis) where the absorbance peak can be observed in the range of 280 to 300 nm. Based on the band gap energy analysis, the NCC/GO thin film has optical band gap of 4.00 eV. Meanwhile, the sensing properties of the NCC/GO thin film shows a good result where metal ions such as copper, zinc, and nickel ion can be detected as low as 0.01 ppm using SPR. Fitting of the SPR curves also reveals the real part refractive index, n and the imaginary part refractive index, k values found for the NCC/GO layer were 1.4240 and 0.2520, respectively with thickness of 9.5 nm. Interestingly when the NCC/GO thin film was exposed to metal ion, a clear change of refractive index and the thickness was observed. The sensitivity of the NCC/GO thin film for copper, zinc, and nickel ion detection was 3.271 ppm−1 , 2.579 ppm−1 , and 1.509 ppm−1 respectively. In addition, the NCC/GO thin film also has high affinity towards copper ion with binding affinity constant of 4.075  103 M-1 compared to zinc and nickel ion at 2.579 ppm−1 and 1.509 ppm−1 respectively. Furthermore, the NCC/GO thin film incorporated with copper ionophore has successfully increased the sensitivity and selectivity for sensing copper ion. When compared with NCC/GO thin film, the NCC/GO-ionophore thin film has much higher sensitivity value of 59.9150° ppm-1 from 0.001 to 0.01 ppm and 2.2261° ppm-1 from 0.01 to 0.1 ppm. Besides that, the NCC/GO-ionophore thin film was able to detect copper ion in spiked water sample as low as 0.5 ppm with sensitivity of 0.01418° ppm-1 from 0.5 to 20 ppm and 9.815  10-3 ° ppm-1 from 20 to 100 ppm. The above results conclude that the developed optical sensor using NCC/GO-ionophore thin film has a good sensitivity and selectivity for copper ion sensing.